2022
DOI: 10.1155/2022/9025354
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Genetic Variations May Associate with the Risk of Developing Late Fracture-Related Infection in the Chinese Han Population

Abstract: Variations in the vitamin D receptor (VDR) gene are related to several inflammatory disorders. However, the potential links between such alternations and the risk of developing late fracture-related infection (FRI) remain unclear. This study investigated associations between genetic variations in the VDR and susceptibility to late FRI in the Chinese Han population. Between January 2016 and December 2019, 336 patients with late FRI and 368 healthy controls were genotyped six VDR genetic variations, including Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…One of the underlying mechanisms rests with the fact that such genetic polymorphisms may affect the serum vitamin D level (Ferraz et al, 2022;Yang et al, 2022), causing different biological effects. With regard to bone infection, previous reports (Jiang et al, 2016;Zhao et al, 2022) have shown definite relationships between VDR gene polymorphisms and the risks of OM development, however, the detailed mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the underlying mechanisms rests with the fact that such genetic polymorphisms may affect the serum vitamin D level (Ferraz et al, 2022;Yang et al, 2022), causing different biological effects. With regard to bone infection, previous reports (Jiang et al, 2016;Zhao et al, 2022) have shown definite relationships between VDR gene polymorphisms and the risks of OM development, however, the detailed mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 95%
“…More important, potential relationships between different genotypes and serum vitamin D levels were not explored, and thus, the effects of genotype on vitamin D level in OM patients is still unknown. While in a subsequent study (Zhao et al, 2022), positive links were found between VDR gene polymorphisms and susceptibilities to FRI, and definite relationships were also obtained between different genotypes and serum vitamin D levels.…”
Section: Introductionmentioning
confidence: 82%
“…Bsm I (rs1544410) is located in intron 8 of the gene and consists in A > G nucleotide substitution, influencing transcript stability. The A nucleotide corresponds to allele B, and the G nucleotide corresponds to allele b. Fok I is a T > C nucleotide substitution on the VDR gene codon start (ATG → ACG) [ 82 , 83 , 84 ]. This shortened protein gains greater transcription activity due to the minor steric bulk of the molecule at the binding site of the transcription factor IIB [ 85 ].…”
Section: Genetic Factors Influencing Vitamin D Homeostasismentioning
confidence: 99%
“…The functional impact of this polymorphism has not yet been clearly described. These polymorphisms are strictly correlated to diseases and changes in homeostasis processes, such as bone mineralization and calcium intake [ 81 , 82 , 84 ]. For example, the VDR gene can interact with calcium in humans [ 83 ].…”
Section: Genetic Factors Influencing Vitamin D Homeostasismentioning
confidence: 99%
“…Growing evidence has demonstrated that vitamin D receptor (VDR) SNVs are involved in the pathogenesis of several inflammatory disorders, such as fracture-related infection[ 73 ], tuberculosis[ 74 ], and periodontitis[ 75 ]. In a 2017 study, Soroush et al [ 76 ] analyzed the role of VDR SNV rs2228570 in the development of DFU in an Iranian population.…”
Section: Genetic Snvs Involved In Dfu Developmentmentioning
confidence: 99%